2017
DOI: 10.18860/jt.v9i2.4733
|View full text |Cite
|
Sign up to set email alerts
|

The Insights of Glocalization In Islamic Primary Education

Abstract: <span style="font-family: BookAntiqua; font-size: 11pt; color: #000000; font-style: normal; font-variant: normal;">The expansion of internationalization has challenged education advancement<span style="font-family: BookAntiqua; font-size: 11pt; color: #000000; font-style: normal; font-variant: normal;"> in 21th century which is not only at Islamic higher education level but also at the Islamic <span style="font-family: BookAntiqua; font-size: 11pt; color: #000000; font-style: normal; font-varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In the Chinese context, questionnaire and interview data on glocalized practices showed that foreign approaches were used particularly when teachers wanted to help students express themselves and share opinions (Pawan & Pu, 2019). A similar approach was used to collect data in Indonesian primary schools (Suci & Puspitasari, 2017), where classroom observations were also added to the analysis. Again, practices labeled as glocalized were those that encouraged students to share opinions and interact, presented and valued diverse perspectives, and used local wisdom to expand students' global knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In the Chinese context, questionnaire and interview data on glocalized practices showed that foreign approaches were used particularly when teachers wanted to help students express themselves and share opinions (Pawan & Pu, 2019). A similar approach was used to collect data in Indonesian primary schools (Suci & Puspitasari, 2017), where classroom observations were also added to the analysis. Again, practices labeled as glocalized were those that encouraged students to share opinions and interact, presented and valued diverse perspectives, and used local wisdom to expand students' global knowledge.…”
Section: Introductionmentioning
confidence: 99%